ANALISIS KALIMAT TANYA DALAM NOVEL MAWAR LAYUKU KARYA KAWÉ ARKAAN - Apriani Ningsih; Erlina Zahar; Sujoko Sujoko (Universitas Batanghari, 2021)
This research aims to describe the types of interrogative sentences in the novel Mawar Layuku by Kawé Arkaan. By using qualitative descriptive research approach, researcher can describe the use of the types of interrogative sentences in Kawé Arkaan's Novel Mawar Layuku, namely regular interrogative sentences, rhetorical interrogative sentences, clarification interrogative sentences, and interrogative question sentences. The results of this research included four types of interrogative sentences: (1) there are 28 expressions of regular interrogative sentences, (2) 48 expressions rhetorical interrogative sentences, (3) 26 expressions of clarification interrogative sentences, (4) 28 expressions of disguised interrogative sentences. Of the four types of interrogative sentences there are 130 citations found, the most dominant type of interrogative sentence used in Kawé Arkaan's Mawar Layuku Novel is the rhetorical interrogative sentence of which occurred 48 times, while the least type of interrogative sentence is the clarification intterogative sentence of 26 quotations.